Cytotoxic effect of Brassica oleracea on liver cancer cell lines - Vanitha V; Pushpabharathi N; Kripa KG; Bothiraj K.V; Murugan K (International Journal of Research in Pharmaceutical Sciences, 2018)
The present study was conducted to evaluate the phytochemical and to assess the anti-carcinogenic activity of Brassica oleracea on hepatocellular carcinoma. The extraction was done using ethanol solvent and the collected extract was analyzed for its phyto-compounds. The presence of flavonoids, terpenoids, tannins, alkaloids, phenols, carbohydrates, glycosides and amino acid were observed. Then the extract was estimated for its total protein content by Lowry's method. The total protein content of 0.2ml and 0.4ml of b ethanol extract were determined to be 10mg and 11.5mg respectively. To justify the anticancer property, Brassica oleracea ethanol extract has been subjected to MTT assay on Hep G2 cell line. The cell viability and cytotoxicity were assessed and IC 50 was calculated to be 40.92ug. To analyze the apoptotic induction CASPASE, 9 activity was measured. It shows the elevated level of caspase 9 on comparing to non-treated Hep G2 cell line. Thus, this present investigation proved that Brassica oleracea ethanol extract possesses phytocompounds that can serve as an efficient anticancer drug on hepatocellular carcinoma without any adverse effect.